A Fluorescent Reporter-Based Evaluation Assay for Antibacterial Components Against Xanthomonas citri subsp. citri - Long, Yunfei; Luo, Ruifang; Xu, Zhou; Cheng, Shuyuan; Li, Ling; Ma, Haijie; Bao, Minli; Li, Min; Ouyang, Zhigang; Wang, Nian; Duan, Shuo (Frontiers in Microbiology, 2022)
Xanthomonas citri subsp. citri (Xcc) is the agent of citrus bacterial canker disease (CBC), which has significantly reduced the quantity and quality of citrus in many citrus-producing worldwide. The copper-based bactericide is the primary product for CBC control, but derivative copper-resistant and environmental contamination problems have been placed on anxiety issues. Thus, there is a need to find alternative antibacterial products instead of dependent on a single type of agent. This study developed a method to evaluate the inhibition of antibacterial agents by using the fluorescent-labeled recombinant Xcc strain (Xcc-eYFP). Optimization of timelines and parameters for antibacterial agents’ evaluation was based on a Spark™ multimode microplate reader. Results showed the minimum inhibitory concentration (MIC) of commercial bactericides determined by bioluminescence agrees with the MIC values determined by the conventional method. Results showed that this evaluation and screening method can be applied for bactericides, cocktail-mixture formulations, antagonistic bacteria, and derived metabolites. Notably, a screened cocktail-mixture bactericides present more active than individual agents during the protective effects. In summary, we provide a validated screening and evaluation method of different antibacterial components for inhibition against Xcc. This method can be developed as a new antibacterial component screening and evaluation to decrease the usage of copper-based bactericides.